The Role of Purchase Intention as an Intervening Variable of Service Quality and Word of Mouth on Purchasing Decisions at PT Berlian Jasa Terminal Indonesia (PT BJTI PORT) - Herlambang, Anggit Julio; Triyonowati, Triyonowati; Prijati, Prijati (International Journal of Business, Law, and Education, 2023)
This study aims to examine and analyze the role of purchase intention as an intervening variable of service quality and word of mouth on purchasing decisions at PT. Berlian Jasa Terminal Indonesia (PT BJTI PORT). Several factors influence the buyer's decision including cultural factors, social factors, personal factors, and psychological factors and there are four factors 1) product, 2) price, 3) promotion, and 4) location. The sampling technique was purposive sampling with a total of 100 respondents. The methodology in this study is descriptive-quantitative using descriptive analysis and inferential statistics, namely, this research analysis of inferential statistical data is measured using WarpPLS version 5.0 PLS (Partial Least Square) software. Based on the results of data analysis regarding direct and indirect influences, it shows that service quality does not influence purchasing decisions, word of mouth influences purchasing decisions, buying interest influences purchasing decisions, and buying interest is unable to intervene or is unable to mediate influence. service quality on purchasing decisions while buying interest can intervene or be able to mediate the influence of word of mouth on purchasing decisions. This means that buying interest can encourage or direct consumers to make purchasing decisions at PT. Berlian Jasa Terminal Indonesia (PT BJTI PORT)